Student’s Self Assessment and Engagement Through the Application of Grammarly AWCF - Joan Chandra Jovando (Universitas Negeri Surabaya, 2024)
The continual development of technology has led to the appearance of many software that could be used in the teaching-learning process. One such type of software is what is known as Automated Writing Evaluation (AWE) tools. AWE tools can support the teaching-learning process by providing what is known as Automated Written Corrective Feedback (AWCF) for its user. Grammarly is one of the AWE tools that has stood out in recent years, gaining popularity worldwide, despite of that, the research done on the effectiveness of student engagement with the AWE tools has remained inconclusive so far. This research will be focused on finding how effective are students able to use Grammarly AWCF. The research will be a qualitative study based on the theoretical framework developed by Zhang and Hyland (2018) about student engagement with AWCF which includes three dimensions: behavioral engagement, emotional engagement, and cognitive engagement. The data will be gathered using a questionnaire, interview, and analyzing a text taken from 10 students 2018 the English Education major chosen through non-probability sampling. The data received from the students will be analyzed using thematic analysis which includes five steps: familiarizing, coding, generating themes, finalizing themes, and writing conclusions from themes. The analyzed data will be presented using descriptive method. The result of the research found that while the students do have a generally positive emotional engagement with the AWCF they received from Grammarly, meaning that they appreciated the feedback, their behavioral and cognitive engagement was rather negative. Most of the students simply accepted the feedback they received from Grammarly without giving it much thought, meaning they couldn’t detect the error that the software missed or they followed the wrong AWCF. This imply that student couldn’t effectively engage with the AWCF they received from AWE tools and that they still needed teacher guidance.